Improved coupling of nanowire-based high-Tc SQUID magnetometers—simulations and experiments. (20th October 2017) - Xie, M; Chukharkin, M L; Ruffieux, S; Schneiderman, J F; Kalabukhov, A; Arzeo, M; Bauch, T; Lombardi, F; Winkler, D
Abstract: Superconducting quantum interference devices (SQUIDs) based on high critical-temperature superconducting nanowire junctions were designed, fabricated, and characterized in terms of their potential as magnetometers for magnetoencephalography (MEG). In these devices, the high kinetic inductance of junctions and the thin film thickness (50 nm) pose special challenges in optimizing the field coupling. The high kinetic inductance also brings difficulties in reaching a low SQUID noise. To explore the technique for achieving a high field sensitivity, single-layer devices with a directly connected pickup loop and flip-chip devices with an inductively coupled flux transformer using a two-level coupling approach were fabricated and tested. Two-level coupling is an approach designed for flip-chip nanowire-based SQUIDs, in which a washer type SQUID pickup loop is introduced as an intermediate coupling level between the SQUID loop and the flux transformer input coil. The inductances and effective areas of all these devices were simulated. We found that at T = 77 K, flip-chip devices with the two-level coupling approach (coupling coefficient of 0.37) provided the best effective area of 0.46 mm 2 among all the tested devices. With a flux noise level of 55 μ Φ 0 Hz − 1 / 2 ⁢, the field sensitivity level was 240 fT Hz − 1 / 2 . This sensitivity is not yet adequate for MEG applications but it is the best level ever reached for nanowire-based high- T c SQUID magnetometers.